The Effect of Chicken Eggs on The Body Weight of Stunting Toddlers Aged 12-59 Months - Anggun Tyasmarawati; Sawitri Dewi (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2025)
Stunting remains a major nutritional health problem among Indonesian children under five, with long-term effects on health and the quality of future generations. One effective intervention is providing supplementary food using locally available sources such as chicken eggs. Eggs are rich in essential macro and micronutrients that meet children’s nutritional needs and can improve body weight. This study aimed to determine the effect of chicken egg consumption on the body weight of stunted children in Sumurkidang Village, Bantarbolang Sub-District, Pemalang Regency. A pre-experimental one-group pretest-posttest design was used, involving 36 stunted children aged 12–59 months selected through purposive sampling. Research instruments included chicken eggs, observation sheets, weighing scales, and child growth monitoring cards (KMS). Data were analyzed using the Wilcoxon signed-rank test. The mean body weight increased from 11.489 kg before to 12.375 kg after 90 days of daily egg consumption, showing a significant effect (p = 0.001). In conclusion, daily consumption of chicken eggs for 90 days significantly increased body weight in stunted children. Mothers are encouraged to provide eggs regularly with varied cooking methods while maintaining food hygiene to prevent infection and support optimal growth.